Characterization of plastic deformation and material flow in ultrasonic vibration enhanced friction stir welding. (June 2015) - Liu, Xiaochao; Wu, Chuansong; Padhy, Girish Kumar
Abstract : Material flow and plastic deformation in ultrasonic vibration enhanced friction stir welding are visualized by employing a special marker material and welding procedure. Based on the results, three methods are developed to evaluate the volume of deformed material, the material flow velocity and the strain/strain rate, and the effect of ultrasonic vibration on the plastic deformation and material flow around the tool is characterized.